Isolation and identification of nitrogen-fixing bacteria in the long-term fertility experiment in irrigated lowland rice ecosystem - Felipe, R. D.; Undan, J. R.; Evangelista, E. V.; Cruz, J. A. (International Journal of Agricultural Technology, 2020)
Nitrogen-fixing bacteria makes up the large percentage of the soil environment and has a great role for plant growth promotion and anti-fungal activities. In this study, sixteen unknown bacteria were isolated from the control plot of NSIC Rc158 rice variety in the Long-Term Fertility Experiment of Philippine Rice Research Institute in Science City of Muñoz, Nueva Ecija. The identification of the purified isolates was confirmed using direct Polymerase Chain Reaction using 16S rDNA gene marker. Six bacterial isolates were successfully identified and matched the identities of Bacillus alkalinitrilicus with 98% identity, Pseudomonas nitroreducens with 100% identity, Streptomyces corchorusii with 100% identity, Actinomadura sp. with 99% identity, Sediminicoccus rosea with 100% identity and Bacillus megaterium with 99% identity. Some of these bacteria were known to be a biocontrol agent, potential biofertilizer and also a good bio-remediator in the field of agriculture. Identification of all the bacteria presented on different rice varieties with different fertilizer input using nifH gene marker were recommended in this study.